Traditional values, beliefs and reliance on indigenous resources for crime control in modern southwest Nigeria (2013)
Traditionally, people from the southwest Nigeria believe and place high premium on the use of indigenous resources for warfare like some other groups in Nigeria. The sustenance of the belief in these values has largely been promoted by the inadequacy of modern policing system and the rising crime rate in our society. It is against this background this paper attempts to examine the prevailing values, belief and practices among the people of the southwest and its utility in the maintenance of local security personnel. This paper also seeks to investigate the potency and efficacy of these indigenous resources in providing security within the community and the invincibility of community guard. Qualitative methodology was used to draw relevant information from the study population while the data were analyzed by ethnographic summaries and content analysis. The choice of this method was in consonance with the functional and control theories on which the study hinged. The result shows indigenous resources are efficacious in certain respects if they are used with caution and due observance of certain fundamental laws